Colorectal Adenoma Subtypes Exhibit Signature Molecular Profiles: Unique Insights into the Microenvironment of Advanced Precancerous Lesions for Early Detection Applications. - Mancuso, Francesco Mattia; Higareda-Almaraz, Juan Carlos; Canal-Noguer, Pol; Bertossi, Arianna; Perera-Lluna, Alexandre; Roehrl, Michael Herbert Alexander; Kruusmaa, Kristi (Cancers, 2025)
Simple Summary: Colorectal cancer originates from benign growths in the colon known as adenomas. Understanding how these adenomas become malignant is crucial to the early detection and prevention of colorectal cancer. This study examines DNA methylation and genetic differences among various types of advanced adenomas to identify potential markers that indicate progression toward cancer. By analyzing DNA methylation patterns, gene copy-number changes, and mutations in these lesions, particular signals and pathways associated with each subtype were found. These discoveries can help refine screening methods to detect distinct adenomas lesions at an early stage. By providing new insights into the initial changes leading to colorectal cancer, these findings may significantly impact approaches to prevention and early intervention strategies. Background: Colorectal cancer (CRC) is characterized by the uncontrolled growth of malignant colonic or rectal crypt epithelium. About 85% of CRCs evolve through a stepwise progression from advanced precancerous adenoma lesions. A better understanding of the evolution from adenoma to carcinoma can provide a window of opportunity not only for early detection and therapeutic intervention but potentially also for cancer prevention strategies. Methods: This study investigates the heterogeneous methylation, copy-number alteration (CNA), and mutation signals of histological adenoma subtypes in the context of progression from normal colon to advanced precancerous lesions (APLs) and early-stage CRC. Results: Differential methylation analysis revealed 2321 significantly altered regions among APLs: 137 hypermethylated regions in serrated vs. tubular, 2093 in serrated vs. tubulovillous, and 91 in tubular vs. tubulovillous adenoma subtypes. The most differentiating pathways for serrated adenomas belonged to cAMP signaling and the regulation of pluripotency of stem cells, while regions separating tubular and tubulovillous subtypes were enriched for WNT signaling. CNA events were mostly present in tubular or tubulovillous adenomas, with the most frequent signals being seen in chromosomes 7, 12, 19, and 20. In contrast, early-stage CRC exhibited signals in chromosomes 7, 8, and 20, indicating different processes between APL and early-stage CRC. Mutations reinforce subtype-level differences, showing specific alterations in each subtype. Conclusions: These findings are especially important for developing early detection or cancer prevention tests trying to capture adenoma signatures.